Behavior of Strengthened RC Columns with CFRP under Biaxial Bending (Journal of Engineering, 2013)
In this work, the behavior of reinforced concrete columns under biaxial bending is studied. This work aims at studying the strengthening of columns by using carbon fiber reinforced polymer (CFRP). The experimental work includes investigation of eight reinforced concrete columns (150*150*500mm) tested under several load conditions. Variables considered in the test program include; effect of eccentricity and effect of longitudinal reinforcement (Ø12mm or Ø6mm). Test results are discussed based on load – lateral deflection behavior, load –longitudinal deflection behavior, ultimate load and failure modes. The CFRP reinforcement permits a complete change in the failure mode of the columns .The effect of longitudinal reinforcement in the case of biaxial bending is more pronounced for strengthened columns than for unconfined columns.